Bevacizumab in first-line treatment of elderly patients with metastatic colorectal cancer: German community-based observational cohort study results - Hofheinz, Ralf (BioMed Central, 2014)
BACKGROUND: To evaluate the efficacy of first-line bevacizumab-based chemotherapy for untreated metastatic colorectal cancer (mCRC) based on age. METHODS: Eligibility criteria focused on M1 disease without prior palliative chemotherapy. Choice of chemotherapy regimen was at the physician’s discretion. Predefined efficacy endpoints were response rate, progression-free and overall survival (PFS, OS). Patients were analysed by age (<70 vs. ≥70 years, <75 vs. ≥75 years). RESULTS: Of 1777 patients, 27% and 12% were ≥70 and ≥75 years, respectively. PFS was shorter in elderly patients (<70 vs. ≥70 years: 10.5 vs. 9.5 months, p = 0.074; <75 vs. ≥75 years: 10.5 vs. 8.9 months, p = 0.00019), as was OS (<70 vs. ≥70 years: 25.8 vs. 22.7 months, p < 0.0008; <75 vs. ≥75 years: 25.8 vs. 20.8 months; p < 0.0001). In the groups <70 and <75 years, PFS was longer in those receiving oxaliplatin-/irinotecan-containing regimens vs. those receiving 5-FU/capecitabine (<70 years: 10.6 vs. 9.0 months; p = 0.0065; <75 years: 10.6 vs. 9.2 months; p = 0.028); no difference in PFS was observed between oxaliplatin-/irinotecan-containing regimens vs. 5-FU/capecitabine regimens in both elderly age-group comparisons (≥70 years: 9.7 vs. 9.2 months; ≥75 years: 8.3 and 9.0 months). CONCLUSION: First-line bevacizumab-based chemotherapies were effective in German mCRC patients ≥75 years of age, but PFS and OS were significantly shorter in this age group vs. younger patients.